BRAND EQUITY IN RURAL MARKETS - Sakshi Shivam; Peto Karoly (Annals of the University of Oradea: Economic Science, 2017)
"Perhaps the most salient factor for the most successful brands is the promise of consistent quality. Whether it's a business or a consumer making a purchasing decision, they want to be sure in this world of endless choice that their decision is the right one."–Rosi McMurray, executive director of strategy, The Brand Union. The word "brand" derives from the Old Norse "brandr" meaning "to burn" - recalling the practice of producers burning their mark (or brand) onto their products. A brand has many accepted definitions according to each researcher associated. A brand can be defined as " a distinguishing symbol, mark, logo, name, word, sentence or a combination of these items that companies use to distinguish their product from others in the market". Most of the under developed and the developing nations have much of the geographical area as rural areas where typically poor people live. For example, in Indian scenario, India has a rural population of 70% who live in near about 620,000 villages across the nation. Though having such a huge population and geographical advantage the rural markets is sharing as least as just 6.6% which is just 8 billion rupees out of 120 billion rupee pool of the total Indian market which clearly shows that the rural markets are to a far extent untouched and also could be understood that there are extreme opportunities the rural India provides to those who understand the market well. Though rural markets are not the most promising area and one cannot have their good market share until the brand is well set into the market and a high equity, once if it’s done rural market has got so much of business to handle. Brand equity plays an important role in marketing as it facilitates the effectiveness of brand extensions and brand introductions. The adoption of a brand is dependent on the trust and loyalty of the customers towards the brand. Branding in rural markets is a difficult task as it is a mass market with diversified emotions and meeting all of them is a critical job. The present article aims at elaborating the brand and the brand equity of products/services with a focus on the rural customers/markets.